Breeding and anther derived lines of rice (Oryza sativa L.) for saline coastal areas of Bangladesh - Rahman, M Sazzadur; Das, Keshob C; Das, Dipok K; Biswas, Kuntal; Chowdhury, M Badrul H; Karim, Nulifer H; Salam, M Abdus; Seraj, Zeba I (Bangladesh Journal of Botany, 2010)
Twenty seven anther culture lines (AC-lines) from rice (Oryza sativa L.) were produced from saline tolerant F2 progeny after crosses between salt tolerant IRRI-derived lines and Bangladesh Rice and advanced up to Double Haploid 3 (DH3) generation. Similarly crossed material, which did not respond to anther culture, was also advanced up to F7. The AC-lines were fully characterized for various salinity tolerance parameters at seedling and reduction division stages. The breeding lines were selected for tolerance again at F4 and advanced on site in the coastal area. DH3 plants were also evaluated for agronomic performance in normal soil. The best performing breeding as well as AC-lines in terms of salinity tolerance and agronomic properties were planted in farmers fields in the Boro season, when salinity levels are the highest in the coastal zones of Satkhira. One anther derived line AC-1 and three breeding lines, BR7076, BR7077 and BR7098 produced high yield under stress conditions, whereas AC-1, BR7076 and BR7077 showed moderate reduction in grain yield compared to non-saline conditions. Considering both tolerance and yield performance in the saline area, AC-1 showed more stability compared to the breeding lines. Key words: Anther culture; Breeding; Salinity stress; Coastal rice; Oryza sativa; Bangladesh DOI: 10.3329/bjb.v39i1.5529 Bangladesh J. Bot. 39(1): 71-78, 2010 (June)